PROPOSTA DE MÉTODO DE PROJETO PERFORMATIVO PARA EDIFÍCIOS ENERGETICAMENTE EFICIENTES - Costa, Lucas Martinez da (2020)
The growing of civil construction in the last decades has defined the buildings as one of the main responsible for the world s electricity consumption. In Brazil, na increase in impacts in the comercial and services sector, such as office buildings, are m